EVALUATING ISLAMIC BANK PERFORMANCE PRE- AND POST-MERGER USING EVA - Eva Ulfah Rahayu; Safrizal; Meilinda Anggreni; Novira Fazri Nanda; Tiara Nurpratiwi (Asosiasi Dosen Muda Indonesia, 2025)
The merger of three state-owned Islamic banks under Himbara—BRIS, BNIS, and BSM—into Bank Syariah Indonesia (BSI) in 2021 represents a pivotal development in the consolidation and strengthening of Indonesia’s Islamic banking industry. This study aims to evaluate and compare the financial performance of Islamic banks in Indonesia before and after the merger by employing the Economic Value Added (EVA) method, which incorporates the Weighted Average Cost of Capital (WACC) to provide a more accurate assessment of value creation. The research period spans from 2018 to 2023, covering three years prior to the merger (2018–2020) and three years following the merger (2021–2023). The findings reveal that EVA values remained negative throughout the entire observation period. However, there was a slight improvement in negative EVA values prior to the merger, whereas a further deterioration was observed in the post-merger period. These results suggest that the merger has not yet led to an enhancement in financial value creation, and they highlight the need for a critical reassessment of BSI’s financial strategies moving forward